Management of depression in diabetes: A review of psycho-social interventions - Balhara, Yatan Pal Singh; Verma, Rohit (Journal of Social Health and Diabetes, 2013)
Diabetes and depression are major public health problems associated with significant burden. They share many commonalities. Both the diseases have a very high prevalence, mortality, and disability. The current article reviews the available evidence on psycho-social interventions in management of depression in diabetes. A literature search was performed using MEDLINE, PubMed, PsycINFO, Embase, and Cochrane Review for English language articles published during 1960-2012. There is limited published literature on role of psycho-social interventions in management of depression among diabetics. The available evidence suggests that psycho-social interventions, particularly CBT, are effective in improving depression in patients with diabetes. However, these interventions are not consistently associated with improvement in markers of glycemia control (HbA1c levels).
Keywords: Cognitive behavioral therapy; collaborative care; depression; diabetes; psycho-social interventions